FROM TRADITION TO MARKET: ACCESSING THE AUTHENTICITY OF SHANTIPUR HANDLOOM PRODUCTS - Choudhury, Jhuma; Thakur, Payal (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The handloom industry of Shantipur, West Bengal, represents a significant repository of India’s textile heritage, renowned for its intricate weaving techniques and culturally embedded designs. However, increasing commercialization and evolving market demands have raised critical questions regarding the authenticity of Shantipur handloom products. This study examines the shifting meaning of authenticity within the context of production, distribution, and consumption. Drawing on qualitative fieldwork, including interviews with weavers, traders, and consumers, as well as analysis of secondary sources, the paper explores how traditional practices are being adapted, preserved, or compromised.The research identifies key factors influencing authenticity, including the introduction of power looms, synthetic materials, and design modifications aimed at mass markets. While such changes enhance economic viability and broaden consumer reach, they simultaneously challenge the integrity of traditional craftsmanship. The study also highlights the role of geographical indication (GI) tagging, institutional support, and artisan knowledge systems in maintaining authenticity.Findings suggest that authenticity in the Shantipur handloom sector is not a fixed attribute but a negotiated construct shaped by economic pressures, cultural values, and market expectations. The paper argues for a balanced approach that integrates innovation with heritage preservation, ensuring both sustainability and cultural continuity. By situating authenticity at the intersection of tradition and market forces, this study contributes to broader discussions on safeguarding intangible cultural heritage in a globalized economy.